2006
DOI: 10.1111/j.1537-2995.2006.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian donor health assessment questionnaire: can it be improved?

Abstract: The current format of the Canadian DHAQ is not optimal for donor attention to specific questions asked as part of a list. The majority of repeat donors are ready for a change in the method of administration of the DHAQ. Studies on donor recall may help guide evidence-based changes to the DHAQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 28 publications
(38 reference statements)
0
35
0
1
Order By: Relevance
“…21 An explanation may be that attention for educational materials or during the screening process is often poor, [22][23][24] implying that questions may therefore be answered in a way not reflecting the true situation. 25 Another possibility is that donors trivialize their sexual experience. 13 Required reading of the definitions in brochures seems to have little effect to improve understanding of the questions.…”
Section: Discussionmentioning
confidence: 99%
“…21 An explanation may be that attention for educational materials or during the screening process is often poor, [22][23][24] implying that questions may therefore be answered in a way not reflecting the true situation. 25 Another possibility is that donors trivialize their sexual experience. 13 Required reading of the definitions in brochures seems to have little effect to improve understanding of the questions.…”
Section: Discussionmentioning
confidence: 99%
“…When blood centers complete BPD reports regarding PDI errors for submission to the FDA, the root cause is most frequently attributed to the donor (S. O'Callaghan, FDA, personal communication, 2010) but this is likely not the complete explanation as to why a particular health history is not disclosed at a donation event and then subsequently revealed by the donor at a future donation event.…”
mentioning
confidence: 99%
“…All of the donors with false‐positive questioning responses had some travel history (except one who misclassified Cuba as Central America), and several indicated that they misunderstood the question to be asking if it had been more than 6 months since they had been there. Although the wording of the question appears clear, less than optimal attention to questions is a common problem encountered by survey methodologists 18 and we have found that donor attention to the Donor Health Assessment Questionnaire tends to be poor 19 . Hence, poor attention to the question seems the most likely explanation for the false‐positive questioning responses and these could be clarified with further questioning.…”
Section: Discussionmentioning
confidence: 77%